Description of two new Bathyaethiops species (Teleostei: Alestidae) from the Congo basin - Moritz, Timo; Schliewen, Ulrich K. (Zootaxa, 2016)
Two new species of Bathyaethiops (Teleostei: Characiformes: Alestidae) are described. Bathyaethiops baka n. sp. is a dwarf species with the largest known specimen being only 24.4 mm SL. The species is characterized by an incomplete squamation and a large humeral spot. Bathyaethiops baka n. sp. is known so far only from the Ngoko River of Southeastern Cameroon, a tributary of the Sangha River in the northern Congo basin. The second species, Bathyaethiops flammeus n. sp., shows a diagnostic spot in front of the dorsal-fin base, which is devoid of melanophores and bright red in life. The species is described from the Bakéré River at Yambula-Bakéré, a locality north-west of Kisangani in the Central Congo basin. Other records of Bathyaethiops flammeus n. sp. from the Tshuapa respectively Ruki River at Boende and Eala, Central Congo basin, suggests a wider geographic distribution. A key to all species of Bathyaethiops is provided.